Health‐related quality of life in patients with cutaneous T‐cell lymphoma?. (3rd August 2018) - Holahan, Heather M.; Farah, Ronda S.; Fitz, Sara; Mott, Sarah L.; Ferguson, Nkanyezi N.; McKillip, Julie; Link, Brian; Liu, Vincent
Abstract: Background: Little is currently known about health‐related quality of life (HRQoL) of patients with cutaneous T‐cell lymphoma (CTCL), a condition characterized by chronic, pruritic, visible lesions, features which may be uniquely influential. Objective: The aim of this study was to establish baseline HRQoL data for patients with CTCL and identify its influencing factors. Methods: Prospective, nonblinded survey design utilizing questionnaires including panels of QoL indices obtained from 105 patients with mycosis fungoides, Sezary syndrome, and CD30+ lymphoproliferative disorder. Chart review correlated QoL with year of disease onset/diagnosis, type/stage of disease, current/past therapies, and medical/psychiatric diagnoses. Results: Psychiatric condition was significantly associated with symptoms ( P < 0.01), emotions ( P < 0.01), and functioning ( P < 0.03) subscales along with overall composite measure ( P < 0.01). High‐grade systemic therapy (OR = 5.28) showed greater increase in odds of a lower health state than low grade (OR = 1.54). The number of medical comorbidities was significantly related to itching ( P < 0.01). Increased age was a protective factor with respect to the emotions ( P < 0.01), functioning ( P < 0.01), and overall composite ( P < 0.01) but not predictive of symptoms. Lower income was associated with higher bother on the symptoms subscale. Conclusions: HRQoL in CTCL appears related to a number of factors, including presence of a psychiatric condition, use of systemic (particularly high grade) therapy, number of medical comorbidities, and income.